FORMULASI SNACK BAR TINGGI ANTIOKSIDAN BERBASIS TEPUNG BIJI KURMA (PHOENIX DACTYLIFERA L.) SEBAGAI UPAYA PENCEGAHAN KANKER - Aretha Swari Salsabila, (2020)
Prevalence of cancer is increasing in the world, including Indonesia. Cancer can be caused by oxidative stress which can be prevented by consumption of antioxidants. Date palm seeds contain antioxidants and can be used as flour as one of the raw materials for making snack bars, which is currently one of the food trends. The purpose of this research was to find the right formulation for snack bars with the addition of date palm flour. There were control formula and three formulas with the addition of date palm flour 10%, 20%, and 30%, respectively. In this research, analysis of chemical properties, physical properties, and organoleptic test were carried out on the snack bar. The results of the organoleptic data were analyzed using Kruskal Wallis and Mann Whitney tests. The chosen formula from this research is F1 with 10% date seeds flour substitution. Analysis results of F1 have 8.75% water content, 1.27% ash content, 7.95% protein, 21.64% fat, 60.39 % carbohydrate, antioxidant activity 34.92%, hardness level 1.922,76 gf, dan hue value 59,12 which means the dominant color is yellow red. This research is expected to be a reference for future research and snack bars can be consumed as healthy snacks.